2021
DOI: 10.21500/20112084.5095
|View full text |Cite
|
Sign up to set email alerts
|

Spanish Validation of the “Life Snapshot Inventory”

Abstract: Introduction: The Life Snapshot Inventory (LSI) is a self-report instrument to measure the meaningful vital, personal, and social directions. It was created in the Functional Analytic Psychotherapy as a continuous evaluation of vital changes in areas of life (family, work, love, spirituality, sexuality, health, etc.). Objective: The aim was to validate its psychometric characteristics for the first time. Method: This study involved 530 participants (average age 33 years), in a Spanish sample. The questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In some way, the instrument reflects a snapshot of his/her life in all of those aspects. This instrument has shown its reliability and sensitivity to changes that are produced by treatment (Ruiz-García et al, 2021). A more extensive review of value assessment instruments can be found in Barney (2017), Barret et al (2019), andSerowik et al (2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some way, the instrument reflects a snapshot of his/her life in all of those aspects. This instrument has shown its reliability and sensitivity to changes that are produced by treatment (Ruiz-García et al, 2021). A more extensive review of value assessment instruments can be found in Barney (2017), Barret et al (2019), andSerowik et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…The exploratory factor analysis showed three main factors: community, closeness and obligations, whose internal consistency levels were .70, .71 and .68, respectively, while the total score was .71, which was similar to that of the English original version. In terms of the concurrent validity, the VLQ showed moderate correlations with the "Personal Values Questionnaire" (Schwartz, 1992) (r= .47), and with the "Life Snapshot Questionnaire (Ruiz-García et al, 2021; Tsai et al, 2023) (r= .65). The usefulness of the VLQ for assessing and tracking key processes involved in clinical change, as well as for enhancing and assessing personal values intimately related to quality of life, meaning in life and community well-being is discussed.…”
mentioning
confidence: 98%